Responding to Refugees in Australia: What is the Christian Response? - Tim Costello; Nils von Kalm (Health for All Nations, 2018)
What role should Christians play in dealing with the march of displaced people across the globe? What moral and spiritual obligations do we owe the distant stranger - the refugee? We can learn from the experience of the Hebrew refugees leaving Egypt and the inclusive nature of the early Christian Church. In the Australian context, this article explores the historical and current attitudes towards asylum seekers and calls for a faith-led movement to stand shoulder to shoulder with those who are demonised and dehumanised.